MTMR4 Is Required for the Stability of the Salmonella-Containing Vacuole - Teo, Wei X.; Kerr, Markus C.; Teasdale, Rohan D. (Frontiers in Cellular and Infection Microbiology, 2016)
The intracellular pathogen Salmonella enterica servovar Typhimurium (S. typhimurium) modulates the host cell’s phosphoinositide (PI) metabolism to establish its intracellular replicative niche, the Salmonella-containing vacuole (SCV). Upon invasion, phosphoinositide 3-phosphate (PI(3)P) and other early endosomal markers are rapidly recruited to and remain associated with the SCV throughout its early maturation. While the phosphoinositide 3-phosphatase myotubularin 4 (MTMR4) has an established role in regulating autophagy and cellular PI(3)P-content, two processes associated with the intracellular survival of S. typhimurium, a direct role for MTMR4 in Salmonella biology has not been examined. Here we demonstrate that GFP-tagged MTMR4 is recruited to the SCV and infection of cells depleted of endogenous MTMR4 results in a decrease in viable intracellular Salmonella. This reflects a significant increase in the proportion of SCVs with compromised integrity, which targets the compartment for autophagy and consequent bacterial cell death. These findings highlight the importance of PI(3)P regulation to the integrity of the SCV and reveal a novel role for the myotubularins in bacterial pathogenesis.